Hypermutation takes the driver’s seat - Schlesner, Matthias; Eils, Roland (Genome medicine, 2015)
Most pediatric tumors have only very few somatic mutations. However, a recent study revealed that a subset of tumors from children with congenital biallelic deficiency of DNA mismatch repair exhibits a mutational load surpassing almost all other cancers. In these ultra-hypermutated tumors, somatic mutations in the proofreading DNA polymerases complement the congenital mismatch repair deficiency to completely abolish replication repair, thereby driving tumor development. These findings open several possibilities for exploiting ultra-hypermutation for cancer therapy.
Gesehen am 25.06.2020